(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 09:09:48
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy](x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy](x-y)[(x+y)^2-xy]+(x-y)[(x-y)^
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]
解
原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)
解:原式=(x-y)[(x+y)^2-xy+(x-y)^2+xy]=(x-y)(2x^2+2y^2)=2(x-y)(x^2+y^2)
解
原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)为什么...
全部展开
解
原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)
收起
(-x-y)(x^2+xy+y^2)
化简x^-y^/x^-2xy+y^
2*(x-y)²(y-x)(xy)
(x^2+xy/x-y)/(xy/x-y)计算
X-Y/2X+2Y XY/X+Y²
因式分解:x×x-xy-2y×y-x-y
(x+y)/x /(x-(2xy-y^2)/x) 因式分解
|x|/x+y/|y|+xy/|xy|=
代数 x^-y^/ x^-(y-z)^ 除以 x^+2xy+y^/(x-y)^-z^ 乘 x^+xy-xz/x^-xy
因式分解:12xy^2(y-x)+xy^3(x-y)+4x^2y(x-y)
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]
x根号x+x根号y/xy-y^2)-(x+根号xy+y/x根号x-y根号)y
xy(x-y)-x(x-y)²
.(x+y-2)(x+y-2xy)+(xy-1)^2
(x^2-xy)y÷y-x/xy怎么做?
[x(x^2y^2-xy)-y(x^2-x^3y)]/(2x^2y)
[x(x^2y^2-xy)-y(x^2-x^3y)]/3x^2y
[x(x^2y^2-xy)-y(x^2-x^3y)]/3x^2y